2016
DOI: 10.18632/oncotarget.11175
|View full text |Cite
|
Sign up to set email alerts
|

CMV70-3P miRNA contributes to the CMV mediated glioma stemness and represents a target for glioma experimental therapy

Abstract: Glioblastoma multiforme (GBM) is a rapidly progressive brain tumor with a median survival of 15–19 months. Therapeutic resistance and recurrence of the disease is attributed to cancer stem cells (CSC). Here, we report that CMV70-3P miRNA encoded by CMV increases GBM CSC stemness. Inhibition of CMV70-3P expression using oligo inhibitors significantly attenuated the ability of primary glioma cells to proliferate and form neurospheres. At the molecular level, we show that CM70-3P increases expression of cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Ulasov et al analyzed the expression profile of HCMV-encoded miRNAs in GBM tissues, notably, the expression levels of CMV70-3p miRNA (miR-UL-70-3p) showed more than 10-fold upregulation in the GBM tissue when compared to control brain tissues. Additional functional studies revealed that overexpression of CMV70-3p can regulate cancer stemness of CD133 positive glioblastoma cell lines, while downregulation of CMV70-3p can abrogate cell migration and invasion of glioma stem cells, which indicating that CMV70-3p may be a contributing factor for GBM [44]. Subsequently, Liang and colleagues found that miR-UL112-3p was also markedly increased in GBM, and elevated miR-UL112-3p levels were significantly correlated with tumor volume, differentiation grade, clinical stage, and prognosis of GBM patients.…”
Section: Expression Profile Of Hcmv-encoded Mirnas In Hcmvinfected Cementioning
confidence: 98%
“…Ulasov et al analyzed the expression profile of HCMV-encoded miRNAs in GBM tissues, notably, the expression levels of CMV70-3p miRNA (miR-UL-70-3p) showed more than 10-fold upregulation in the GBM tissue when compared to control brain tissues. Additional functional studies revealed that overexpression of CMV70-3p can regulate cancer stemness of CD133 positive glioblastoma cell lines, while downregulation of CMV70-3p can abrogate cell migration and invasion of glioma stem cells, which indicating that CMV70-3p may be a contributing factor for GBM [44]. Subsequently, Liang and colleagues found that miR-UL112-3p was also markedly increased in GBM, and elevated miR-UL112-3p levels were significantly correlated with tumor volume, differentiation grade, clinical stage, and prognosis of GBM patients.…”
Section: Expression Profile Of Hcmv-encoded Mirnas In Hcmvinfected Cementioning
confidence: 98%
“…102 Some recent studies have continued to address this question of tumor modulation, in particular with regard to the effect of CMV-derived determinants on the maintenance or progression of GSCs. 104,107 Recent evidence intriguingly points to the role of neuronal activity in promoting glial oncogenesis. 108,109 Using optogenetic neurostimulation, neuroligin-3 was identified as a secreted synaptic protein that drives the PI3K-mTOR pathway in xenografted high-grade glioma.…”
Section: Selected Environmental Factorsmentioning
confidence: 99%
“…The human glioma U87MG (CVCL_0022) and U251 (CVCL_0021) cell lines were purchased from the American Type Culture Collection (Manassas, VA). The primary patient‐derived GBM1, GBM7 and GBM13 cells were prepared from specimens obtained at the N.N. Blokhin Cancer Research Center (Moscow, Russia), GBM6, GBM12 and GBM43 was obtained from the Department of Neurological Surgery (Northwestern University, Chicago, IL) and GBM56 and GBM57 were obtained from The Brain Tumor Cancer Center (University of Chicago, Chicago, IL).…”
Section: Methodsmentioning
confidence: 99%